Can occupational skills explain the gender wage gap in a developing economy? Evidence from an unconditional quantile regression approach - Andlib, Zubaria (Publishing House of Wroclaw University of Economics and Business, 2025)
Aim: This study investigated the gender wage gap across occupational groups in Pakistan differentiated by their skill level. The author intended to explore how wage disparities between men and women vary across low, average, high, and very high-skilled occupations and examines the presence of structural barriers such as the glass ceiling. Methodology: The study utilised nationally representative microdata from the Pakistan Labour Force Survey (2020-2021) and applied Oaxaca-Blinder decomposition techniques along with unconditional quantile regression models. Results: The empirical findings indicate that women earn significantly lower wages in low and average-skilled occupations compared to their male counterparts. Conversely, women attain wage parity or enjoy a relative advantage in high and very high-skilled occupations. Nonetheless, evidence of glass ceiling effects persists in low, average, and very high-skilled groups, suggesting that human capital differences alone do not fully explain gender-based wage disparities. Implications and recommendations: A multi-pronged approach is necessary to reduce the gender wage gap. Policymakers should strengthen labour market regulations, raise minimum wages, enforce equal pay legislation, and promote gender-inclusive work environments. Encouraging women’s participation in high-skilled occupations through targeted training, mentorship, and flexible work arrangements is essential for sustained wage equality. Originality/Value: This study makes a novel contribution by examining gender wage disparities across occupational skill levels in a developing country using recent data. It also offers disaggregated insights beyond aggregate wage gap estimates, providing actionable evidence for policymakers addressing gender inequality in labour markets across the Global South.
Argumenta Oeconomica, 2025, Nr 2 (55), s. 161-180
Keywords: gender wage gap; skill levels; occupations; glass ceiling